Gambaran Kepatuhan Karyawan Terhadap Penggunaan Alat Pelindung Diri Di PT. Rekind Daya Mamuju - Herman, Surya Pratama; Adiningsih, Ridhayani; Akbar, Fajar (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2025)
The high number of accidents and occupational diseases in the workplace is a problem that must be considered. One way to prevent accidents and occupational diseases is by using PPE. Based on data on work accident cases in west Sulawesi from 2021 to 2023, the number of work accident cases was recorded as many as 80 cases. This study was conducted in january-june 2024 at PT. Rekind Daya Mamuju. The research method used in this study is a descriptive research method. Determination of the sample in this study used the purposive sampling method with the criteria, workers who work in an environtment that produces potential hazard, and workers who are willing to be samples in this study. The data collection technique used was by conducting interviews using a questionnaire. Based on the data and results of the analysis carried out, it’s known that employees of the PT. Rekind Daya Mamuju comply with the use of PPE. This can be seen from the cnowladge, attitudes, and actions of employees regarding the use of PPE which is very good with a percentage of 100%. The conclusion of this study is compliance with the use of Personal Protective Equipment for employees at PT. Rekind Daya Mamuju can be said to be good, seen from the result of interviews regarding employees cnowladge, attitudes, and acion which are very good as much as 100%. The suggestion from this study is for employees to continue to improve their compliance in using PPE, and for the company to continue to supervise the use of PPE.